3D long-range ordered porous ceramics prepared by a novel bidirectional freeze-casting technique. Issue 5 (1st April 2018) - Hu, Zhi-Jie; Shen, Xiang-Tian; Geng, Shu-Li; Shen, Ping; Jiang, Qi-Chuan
Abstract: We developed a novel and simple bidirectional freeze-casting technique to prepare porous ceramics with long-range ordered lamellar structures in three dimensions (3D). A side copper or stainless-steel plate was used as the cold source to generate dual temperature gradients for the control of the nucleation and growth of ice crystals. The Al2 O3 architectures prepared with the side copper plate exhibited well-assembled lamellar structures with abundant cross connections of the ceramic lamellae. The compressive strength of the resultant Al2 O3 architectures with ∼ 50% porosity reached 158 ± 3 MPa in the primary freezing direction and 42 ± 6 MPa in the secondary freezing direction, ∼ 32% and ∼ 130% higher than that of the counterparts prepared by unidirectional freeze casting. In contrast, the Al2 O3 architectures prepared with a side stainless-steel plate exhibited thicker ceramic lamellae and wider pore channels as well as decreased cross connections, leading to much weaker compressive strength.